2021
DOI: 10.3390/v13122335
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Avian-like M1 Plays More Important Role than M2 in Pathogenicity of 2009 Pandemic H1N1 Influenza Virus in Mice

Abstract: Reassortant variant viruses generated between 2009 H1N1 pandemic influenza virus [A(H1N1)pdm09] and endemic swine influenza viruses posed a potential risk to humans. Surprisingly, genetic analysis showed that almost all of these variant viruses contained the M segment from A(H1N1)pdm09, which originated from Eurasian avian-like swine influenza viruses. Studies have shown that the A(H1N1)pdm09 M gene is critical for the transmissibility and pathogenicity of the variant viruses. However, the M gene encodes two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Jianmei [32] reported that both M1-41V and M2-27 contribute to replication and pathogenicity. Our previous study indicated that both M1 and M2 of the CA09 strain affects the virulence when a gene segment is exchanged with the H3N2 swine influenza virus [26]. In the present study, we focused on the M2 protein of the (H1N1)pdm09 virus and its role in pathogenicity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Jianmei [32] reported that both M1-41V and M2-27 contribute to replication and pathogenicity. Our previous study indicated that both M1 and M2 of the CA09 strain affects the virulence when a gene segment is exchanged with the H3N2 swine influenza virus [26]. In the present study, we focused on the M2 protein of the (H1N1)pdm09 virus and its role in pathogenicity.…”
Section: Discussionmentioning
confidence: 95%
“…The wild-types CA09 (CA09-M2-WT) and CA09-M2-E79K were then rescued as previously described [24]. The reverse genetic system of CA09 and the plasmid with the full-length M gene of TX98 were generously provided by Dr. Qinfang Liu from the Shanghai Veterinary Research Institute [25,26]. The two viruses were propagated and titrated on MDCK cells.…”
Section: Plasmid Construction and Virus Rescuementioning
confidence: 99%
See 1 more Smart Citation